Remittances, Trade Balance and Economic Growth in West Africa Sub-region - John Norense Izevbigie; Nosakhare Liberty Arodoye; Beatrice Omo-Ikirodah (Faculty of Economics, Universitas Sriwijaya, 2021)
Owing to the domestic economic wide effect of remittances and trade balances, this study examined their impacts in relation to economic growth in West Africa sub-region with secondary data spanning the period 2007 to 2019 using system generalised method of moment estimation technique. Prior to estimation, reliability and validity of the data set was examined. This was followed by unit root test which shows that variables attained stationarity at their first difference while Co-integration test indicated that there exists a long-run convergence among the variables. The result showed that remittances inflows significantly and positively impact economic growth while trade balance exerted a negative and significant impact on economic growth. The over-identifying restrictions test of Jstatistics showed that the instrument of measurement employed is valid. It was recommended among others that policy makers in West Africa should implement policies that continually encourage remittances inflow and export of goods and services.